Acacetin exerts antitumor effects on gastric cancer by targeting EGFR - Zhang, Guangtao; Dong, Jiahuan; Lu, Lu; Liu, Yujing; Hu, Dan; Wu, Yuanmin; Zhao, Aiguang; Xu, Hanchen (Frontiers in Pharmacology, 2023)
Abstract Background: Gastric cancer (GC) is a common malignant tumor with a poor prognosis. Combination treatments may prolong the survival of patients with GC. Acacetin, which is a flavonoid, exerts potent inhibitory effects on several types of cancer cells; however, the mechanisms of action remain poorly understood. Methods: Network pharmacology and RNA sequencing were used to predict the targets of acacetin, which were then verified by drug affinity responsive target stability (DARTS), cellular thermal shift assay (CETSA) and molecular docking. The biological functions of acacetin in MKN45 and MGC803 cells were investigated using TUNEL assays, crystal staining and colony formation assays. The pathways affected by acacetin were verified through reverse experiments. The in vivo antitumor efficacy of acacetin was assessed in a subcutaneous xenotransplanted tumor model. Results: In this study, we identified EGFR from more than a dozen predicted targets as a protein that directly binds to acacetin. Moreover, acacetin affected the level of phosphorylated EGFR. In vitro, acacetin promoted the apoptosis of GC cells. Importantly, EGFR agonists reversed the inhibitory effects of acacetin on the STAT3 and ERK pathways. In vivo, acacetin decreased the protein levels of pEGFR in tumors, resulting in increased GC xenograft tumor regression without obvious toxicity. Conclusion: Our findings highlight EGFR as one of the direct targets of acacetin in GC cells. Acacetin inhibited the phosphatase activity of EGFR in vitro and in vivo, which played a role in the antitumor effects of acacetin. These studies provide new evidence for the use of acacetin as a potential reagent for the treatment of GC.